El estrés y su incidencia en el clima laboral en los servidores públicos del GAD cantón Tosagua periodo 2021 - Bone Gamez, Luis Alberto (2023)
The objective of this research work was to determine stress and its impact on the working environment of public servants of the Autonomous Decentralised Government of the Tosagua Canton during the period 2021 and the proposal of an improvement plan that would allow institutional strengthening. For the development of the work a mixed research was proposed, where through techniques such as the interview and the survey, data were collected and used for the analysis. The population studied were the workers of the municipal council composed of 254 persons of different positions in the institution, for the collection of information it was necessary an interview applied to the public servants of the GAD of Tosagua, also a survey was executed with the questionnaire proposed by the International Labour Organization-World Health Organization that was directed to the director of human talent, through which it was determined that the level of stress was 4.52% which places it on a scale of moderate to high, which varies depending on the time of year in which it is found; In addition, it was determined that there is no significant correlation between work stress and the organisational climate due to the fact that the stress of the workers responds to external and internal factors.